Regulation of ferroptosis by bioactive phytochemicals: Implications for medical nutritional therapy - Zheng, Kai; Dong, Yun; Yang, Rong; Liang, Youfang; Wu, Haiqiang; He, Zhendan (Pharmacological research, 2021)
Ferroptosis is an iron- and lipotoxicity-dependent regulated cell death that has been implicated in various diseases, such as cancer, neurodegeneration and stroke. The biosynthesis of phospholipids, coenzyme Q10, and glutathione, and the metabolism of iron, amino acids and polyunsaturated fatty acid, are tightly associated with cellular sensitivity to ferroptosis. Up to now, only limited drugs targeting ferroptosis have been documented and exploring novel effective ferroptosis-modulating compound is needed. Natural bioactive products are conventional resources for drug discovery, and some of them have been clinically used against cancers and neurodegenerative diseases as dietary supplements or pharmaceutic agents. Notably, increasing evidence demonstrates that natural compounds, such as saponins, flavonoids and isothiocyanates, can either induce or inhibit ferroptosis, further expanding their therapeutic potentials. In this review, we highlight current advances of the emerging molecular mechanisms and disease relevance of ferroptosis. We also systematically summarize the regulatory effects of natural phytochemicals on ferroptosis, and clearly indicate that saponins, terpenoids and alkaloids induce ROS- and ferritinophagy-dependent ferroptosis, whereas flavonoids and polyphenols modulate iron metabolism and nuclear factor erythroid 2-related factor 2 (NRF2) signaling to inhibit ferroptosis. Finally, we explore their clinical applications in ferroptosis-related diseases, which may facilitate the development of their dietary usages as nutraceuticals. [Display omitted]